أثر كفاية رأس المال والسيولة على الاعتمادات المستندية في المصارف الاسلامية دراسة حالة مصرف سوريا الدولي الإسلامي - حوراني أكرم; اليونس رامي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدراسة الى التعرف على الاثر الذي تلعبه كل من كفاية رأس المال والسيولة في الاعتمادات المستندية لدى مصرف سوريا الدولي الإسلامي، حيث تناول الجانب النظري مفهوم كل من كفاية رأس المال والسيولة وأهمية كل منهم بالنسبة للقطاع المصرفي، بالإضافة إلى مفهوم الاعتمادات المستندية وأنواعها واطرافها ، وقد أُجريت هذه الدراسة خلال الفترة المُمتدة من (الربع الاول للعام2008 وحتى الربع الأخير للعام2012). وأظهرت نتائج اختبار الفرضيات أنه يوجد أثر لكل من كفاية رأس المال والسيولة(الجاهزية النقدية) على الاعتمادات المستندية لدى مصرف سوريا الدولي الإسلامي ، حيث أدّى الاحتفاظ بنسب مرتفعة من كفاية رأس المال والسيولة الى انخفاض حجم الاعتمادات المستندية لدى مصرف سوريا الدولي الإسلامي خلال فترة الدراسة، وبناءً عليه أوصت الدراسة بضرورة الموازنة بين الاحتفاظ بنسب كفاية رأس المال والسيولة وبين إمكانية استثمار تلك الأموال في تحقيق ارباح مُحتملة من خلال عوائد الاعتمادات المستندية . This study aimed to identify the effect played by both capital adequacy and liquidity in the documentary credits to Syria International Islamic Bank . Where he addressed the theoretical concept of both capital adequacy and liquidity, and the importance of each of them for the banking sector ,In addition to the concept of documentary credits, types and its parties, this study was conducted during the period (first quarter of 2008 to the fourth quarter of 2012). The results showed test hypotheses that there is the impact of both capital adequacy and liquidity (cash Readiness) on documentary credits to Syria International Islamic Bank. Where it caused retain high rates of capital adequacy and liquidity to the low volume of documentary credits to Syria International Islamic Bank during the study period. Accordingly, the study recommended the need to balance the retention rates of capital adequacy, liquidity and the ability to invest those funds in achieving the potential profit through returns documentary credits.